What Happened to Our Environment and Mental Health as a Result of Hurricane Sandy?. (18th April 2016) - Lin, Shao; Lu, Yi; Justino, John; Dong, Guanghui; Lauper, Ursula
Abstract: Objectives: This study describes findings of the impacts of Hurricane Sandy on environmental factors including power outages, air quality, water quality, and weather factors and how these affected mental health during the hurricane. Methods: An ecological study was conducted at the county level to describe changes in environmental factors—especially power outages—and their relationships to emergency department (ED) visits for mental health problems by use of a Poisson regression model. Results: We found that many environmental hazards occurred as co-exposures during Hurricane Sandy in addition to flooding. Mental health ED visits corresponded with the peak of maximum daily power blackouts, with a 3-day lag, and were positively associated with power blackouts in Bronx (prevalence ratio [PR]: 8.82, 95% confidence interval [CI]: 1.27–61.42) and Queens (PR: 2.47, 95% CI: 1.05–5.82) counties. A possible dose-response relationship was found between the quantile of maximum blackout percentage and the risk of mental health in the Bronx. Conclusion: We found that multiple co-environmental hazards occurred during Hurricane Sandy, especially power blackouts that mediated this disaster's impacts. The effects of power outage on mental health had large geographic variations and were substantial, especially in communities with low sociodemographic status. These findings may provide new insights for future disaster response and preparedness efforts. ( Disaster Med Public Health Preparedness . 2016;10:314–319)